Evaluation of the Safety and Immunogenicity of Fractional Intradermal COVID-19 Vaccines as a Booster: A Pilot Study - Suvimol Niyomnaitham; Somruedee Chatsiricharoenkul; Zheng Quan Toh; Sansnee Senawong; Chatkamol Pheerapanyawaranun; Supaporn Phumiamorn; Paul V. Licciardi; Kulkanya Chokephaibulkit (Vaccines, 2022)
Intradermal vaccination using fractional dosages of the standard vaccine dose is one strategy to improve access to COVID-19 immunization. We conducted a pilot study in healthy adults in Thailand to evaluate the safety and immunogenicity of intradermal administration of fractional doses of ChAdOx1 (1/5th of standard dosage) or BNT162b2 (1/6th of standard dosage) to individuals previously vaccinated (prime) with two-dose intramuscular CoronaVac, ChAdOx1 or BNT162b2. Following an initial immunogenicity exploratory phase for each vaccine combination group (n = 10), a total of 135 participants (n = 45 per group) were recruited to 3 groups (CoronaVac prime-intradermal BNT162b2 boost, CoronaVac prime-intradermal ChAdOx1 boost and ChAdOx1 prime-intradermal BNT162b2 boost) and their immunogenicity data were compared to a previous cohort who received the same vaccine intramuscularly. Two weeks following booster vaccination, neutralizing antibodies against the delta variant were similar between the participants who received intradermal and intramuscular vaccination. However, neutralizing antibodies against the omicron variant in the intradermal BNT162b2 boost groups were ~6-fold lower, while the levels in the ChAdOx1 boost group were similar compared to their respective vaccine regimen given intramuscularly. The intradermal booster significantly increased spike-specific T cell responses in all three groups from pre-booster levels. Local and systemic adverse reactions were milder in intradermal compared to intramuscular injections. Further studies are needed to evaluate the clinical relevance of these findings and the feasibility of administration of intradermal COVID-19 vaccines.